2004
DOI: 10.1213/01.ane.0000093234.30458.d1
|View full text |Cite
|
Sign up to set email alerts
|

Pyloromyotomy in a Patient with Paramyotonia Congenita

Abstract: The literature concerning general anesthesia in paramyotonic patients is limited. We report a case of paramyotonia congenita in a 2-mo-old male infant undergoing surgery for pyloric stenosis and inguinal hernia after an uneventful anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Mutated sodium channels which result in an increased tendency to generate repetitive action potentials and muscle fibers depolarization, have been described (12). An abnormal gene on chromosome 17q, which encodes the α ‐subunit of human skeletal muscle sodium channel, may be responsible for these diseases (13). The likelihood of these disorders in this patient is quite small since family history is negative, exposure to cold temperatures did not occur, and rigidity was not reported with succinylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…Mutated sodium channels which result in an increased tendency to generate repetitive action potentials and muscle fibers depolarization, have been described (12). An abnormal gene on chromosome 17q, which encodes the α ‐subunit of human skeletal muscle sodium channel, may be responsible for these diseases (13). The likelihood of these disorders in this patient is quite small since family history is negative, exposure to cold temperatures did not occur, and rigidity was not reported with succinylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…Later in life, these individuals may also elicit transient disabling paralysis following such episodes of myotonia . It has been reported that volatile anesthesia using sevoflurane has been used repeatedly in PC patients without any incident and the risk of susceptibility to MH was considered to be that of the general population . In both reported cases of anesthetic induction for the PC patient, the protocols did not use muscle relaxants.…”
Section: Sodium Channelopathies: Hyperkalemic Periodic Paralysis Parmentioning
confidence: 99%
“…In both reported cases of anesthetic induction for the PC patient, the protocols did not use muscle relaxants. It should be noted that especially the use of succinylcholine is contraindicated in such cases, as potential increases in serum potassium concentrations could trigger myotonic symptoms . Furthermore, one should refrain from administering anticholinesterase agents or supplementing potassium, as these may provoke severe myotonia.…”
Section: Sodium Channelopathies: Hyperkalemic Periodic Paralysis Parmentioning
confidence: 99%
“…Mutant channels exhibit sustained sodium currents that lead to prolonged membrane depolarization, causing myotonia, followed by membrane desensitization (or inactivation), resulting in paralysis. Clinically, this disorder is characterized by transient stiffness (myotonia) precipitated by exposure to such factors as cold temperatures or physical exertion.Several case reports of anesthesia employed for patients with PC have been published [1][2][3], and below we describe our experiences with anesthesia employed for a PC patient who underwent a subtotal gastrectomy for treatment of a gastric carcinoma. …”
mentioning
confidence: 99%
“…Several case reports of anesthesia employed for patients with PC have been published [1][2][3], and below we describe our experiences with anesthesia employed for a PC patient who underwent a subtotal gastrectomy for treatment of a gastric carcinoma.…”
mentioning
confidence: 99%